Estimation of residue of carbendazim in harvested mushroom fruiting bodies form the treated substrate in Pleurotus spp. - Pegu, Lunisha; Sarmah, D K (Mushroom Research, 2021)
An experiment was conducted to assess the amount of residue present in the mushroom fruiting body harvested from the beds treated with formaldehyde and carbendazim against microbial contaminants. Different species of Pleurotus viz., P. sajor-caju, P. sapidus and a commercial hybrid was used for the experiment. The different concentration levels of formaldehyde and carbendazim was at the rate of 500 ppm formaldehyde + 10 ppm carbendazim, 750 ppm formaldehyde + 20 ppm carbendazim, 1000ppm formaldehyde + 30 ppm carbendazim, 1250 ppm formaldehyde + 40 ppm carbendazim, 1500 ppm formaldehyde + 50 ppm carbendazim, 1750 ppm formaldehyde + 60 ppm carbendazim, 1000 ppm formaldehyde, 40 ppm carbendazim were applied for managing the contaminants. The investigation revealed that the residue of carbendazim present in mushroom fruiting body was least in the concentration at the rate of 40 ppm carbendazim in P. sajor-caju, 60 ppm carbendazim combined with1750 ppm formaldehyde in P. sapidus, 70 ppm carbendazim combined with 2000 ppm formaldehyde and 40ppm carbendazim in commercial hybrid. The maximum residue was found in the concentration at the rate of 30 ppm carbendazim combined with 1000 ppm formaldehyde in P. sajor-caju and P.sapidus and 40 ppm carbendazim combined with 1250 ppm formaldehyde in commercial hybrid.